Liberating narratives of Yaşar Kemal: The Other Face of the Mountain trilogy - Bico, Cem. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2006., 2006)
This thesis aims to show how the novels of Yaşar Kemal comprising The Other Face of the Mountain trilogy-The Wind from the Plain (1960), Iron Earth, Copper Sky (1963) and The Undying Grass (1968)-function as "liberative narratives". After a literature review focusing on the interpretations of the author's works based on the concept of reality and his own assertions regarding the issue, an analysis of the novels under focus provides the characteristics of the social setting in the novels and the themes whereby the liberating effect is created. Finally, the basic principles underlying the liberating qualities of the narratives are shown through an analysis of how they are constructed and related to the social context and how these narratives call the readers for political activity. It is argued that the covering of subjectivities of the protagonists-and culture as the subjectivity of the community-as factors making the objective reality in various ways, enables the author to convey the possibility of human agency. This approach sees culture as a practice. Moreover, the actualization of moral tensions within the narrative, which are formed around humanist-socialist social values, also serves to the liberating ends of the author by allowing him to convey an ethical stance that is necessary for a notion of liberation. These novels of Yaşar Kemal function as liberating narratives in portraying a reality made by human beings, a socialist ethics that is actual and through the use of experience-oriented formal literary tools.
Keywords: Authors, Turkish -- 20th century.